2023
DOI: 10.5296/jpag.v13i1.20693
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Corporate Governance Practices on Non-Performing Loans in Iraqi Banks; The Moderating Effect of Concentrated Ownership

Abstract: This study aims to examine the connection between corporate governance mechanisms and non-performing loans (NPLs) using agency theory. In addition, the study examines the moderating effect of concentrated ownership (CO) between NPLs and financial distress. The study adopts a sample of 42 Iraqi banks from 2017–2021 with 210 observations. Panel estimation utilised a regression estimator to test the research hypotheses of the study. Three regression models were used to test the hypotheses after obtaining the appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…As well as, shareholders have the authority to observe managers [50]. Eventually, enhance firm performance [5,51]. As such, by using 300 Indonesian firms [52] showed that firms with concentrated ownership have high audit quality.…”
Section: Concentration Ownership and Audit Qualitymentioning
confidence: 99%
“…As well as, shareholders have the authority to observe managers [50]. Eventually, enhance firm performance [5,51]. As such, by using 300 Indonesian firms [52] showed that firms with concentrated ownership have high audit quality.…”
Section: Concentration Ownership and Audit Qualitymentioning
confidence: 99%